Study of Quality Changes and Determination of Water Pollution Index At River watershed Bengkulu - Supriyono, Supriyono; Utaya, Sugeng (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Bengkulu Eksisting problematic conditions on water quality. Seeing the importance of water quality because it is the only source of mineral water Bengkulu city in which the water flowing from the fountain in Central Bengkulu Regency. Context territory that includes two administration (city of Bengkulu and Central Bengkulu District) causing the water quality is not controlled and there is no valid data for data management of the waters of the river basin. So the purpose of this study to analyze the quality of river water in the river watershed segmentation Bengkulu. In order to obtain the level of water quality and water pollution index of a river that became a trend among regions and be detail data for watershed management policies. This study was conducted to test the water quality of the physical parameters, chemical and biological by comparing the results of laboratory tests of water quality 2 seasons. This method is very good for being able to analyze and describe the trend of changes in water quality in the watershed Bengkulu. Data obtained from secondary data and primary data. Secondary data is the result of testing during the dry season. Primary data are data that represent the results of field tests of the rainy season. After the data collected then do the test according to river water quality standards appropriate Government Regulation No.82 of 2001 each parameter water. Then calculated the level of pollution in accordance with the model storet Minister of Environment Decree 115 of 2003. Based on exposure to the above results it can be concluded that the water quality in the watershed physically Bengkulu river water during the rainy season and dry season condition with variations in color and turbidity is murky brownish with no difference significant changes in temperature. Chemical and Biological water quality is a significant change in the elements of the TSS, BOD5, COD, and metal content (Fe, Mn, and Cu) which exceeds the limit of the watershed water quality standard Bengkulu. These changes will have an impact on water biota that live in the river because of the water conditions so. So it can be seen that the river water biota disrupted by the changes in the water. Indications are some companies that exist in mines and factories dump wastes in the river. The quality of water exceeds the water quality standards in the segment of river watershed upstream section that is affected by the mining activities and encroachment of forests due to agricultural extension ie oil palm plantations by the community. While in the Central Part of the watershed is affected by rubber and palm oil processing plant palm. Bengkulu watershed-level water contamination, that the river is heavily polluted with values ​​exceeding water quality standards of pollution. Pollution caused by the exploitation of mining and agricultural extension in DAS Bengkulu give clear results that Bengkulu river is heavily polluted with an indicator that the water turbidity never be above normal during the rainy season and the dry season and the area of ​​the river segment.